Handbook for classical research - Schaps, David M. (Taylor & Francis, 2010)
Offers guidance to students needing to learn about the different fields and subfields of classical research, and its methods and resources. This book is divided into 7 parts: The Basics, Language, The Traditional Fields, The Physical Remains, The Written Word, The Classics and Related Disciplines, The Classics since Antiquity.